A New Testing Method for Lifetime Prediction of Automotive Exhaust Silencers. (22nd May 2011) - Yasir, Muhammad; Mori, Gregor; Wieser, Helmut; Schattenkirchner, Martin; Hogl, Manuel
Abstract : The purpose of this paper is to highlight the problems associated with daily routine corrosion tests performed in an automotive exhaust industry. Estimation of the life time of a complete system under real conditions is always uncertain and often leads to a disagreement. A new testing setup was built in which simulation of external and internal corrosion with additional thermal cycles can be performed simultaneously. Simulation of all real conditions makes this test totally versatile and unique among all the existing testing methods. All test results were investigated quantitatively and a direct comparison was made between some field systems with different mileage and total life. Conformity was accomplished between the results from corrosion tests and parts from the vehicles. Studies carried out on the silencers have shown that the new component testing method could be used for life time estimation of parts having different material and design combinations. On the basis of obtained results it can be stated that the new testing setup can be applied for different materials and design rankings.